The Role of Faculty Members at the University of Jordan in Enhancing Intellectual Security among Students - Mamon Alzboon; Ziyad Algonmeen; Malik Alzboon; Azzam Alrefai (المجلة العربية لضمان جودة التعليم الجامعي, 2018)
The aim of this study was to identify the role of faculty members at the University of Jordan in enhancing the concepts of intellectual security in the students' view, from the point of view of faculty members. The study population consisted of (167) faculty members from the Faculty of Education at the University of Jordan during the academic year 2015/2016, who were all selected. The study followed the survey descriptive method. A questionnaire specially developed for this purpose was used. The results of the study showed that the role of faculty members in the Faculty of Educational Sciences / University of Jordan in enhancing the intellectual security of its students was high. The results indicated that there were no statistically significant differences at (0.05)) (0.05 α) in the degree of enhancing intellectual security from the point of view of the teaching staff according to the experience variable. There are significant differences at (0.05 α) level in the degree of enhancing intellectual security from the point of view of the teaching staff according to the age variable. The study recommended the inclusion of concepts related to intellectual security, especially moderation and itidal in Islam in the curriculum, taking into account the smoothness and attractiveness of presentation as well as co-curricular practical activities, which should be done to deepen these concepts in the students. More educational studies on intellectual security covering its dimensions and principles should also be encouraged. Further, there should be emphasis on the roles of educational institutions in enhancing intellectual security.